Thrombocytopenia model with minimal manipulation of blood cells allowing whole blood assessment of platelet function. (18th May 2016) - Skipper, Mette Tiedemann; Rubak, Peter; Larsen, Ole Halfdan; Hvas, Anne-Mette
Abstract: In vitro models of thrombocytopenia are useful research tools. Previously published models have shortcomings altering properties of platelets and other blood components. The aim of the present study was to develop a whole blood method to induce thrombocytopenia with minimal manipulation, and to describe platelet function in induced thrombocytopenia in individuals with healthy platelets. Hirudin anticoagulated blood was obtained from 20 healthy volunteers. One part of the blood was gently centrifuged at 130 g for 15 minutes. The platelet-rich plasma was replaced with phosphate-buffered saline to establish thrombocytopenia. Various levels of thrombocytopenia were achieved by combining different volumes of baseline whole blood and thrombocytopenic blood. Platelet counts were measured by flow cytometry (Navios, Beckman Coulter) and routine haematological analyser (Sysmex XE-5000). Platelet function was analysed by impedance aggregometry (Multiplate® Analyzer, Roche) and by flow cytometry (Navios, Beckman Coulter) using collagen, adenosine diphosphate, thrombin receptor activating peptide-6 and ristocetin as agonists. Median baseline platelet count was 227×10 9 /l. The in vitro model yielded median platelet counts at 51×10 9 /l (range 26–93×10 9 /l). We observed minor, yet significant, changes in platelet size and maturity from baseline to modelled thrombocytopenia. In the thrombocytopenic samples, significant and positive linear associations were found between platelet count and platelet aggregation across all agonists (all p -values<0.001). Platelet function assessed by flow cytometry showed minimal alterations in the thrombocytopenic samples. A new whole blood-based model of thrombocytopenia was established and validated. This new model serves as a useful future tool, particularly to explore platelet function in patients with thrombocytopenia.